PENDIDIKAN SPIRITUAL JAWA-ISLAM R. Ng. RONGGOWARSITO TAHUN 1802-1873 - Aziz, Safrudin (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2017)
Spiritual education-Java version of Islam in this paper emphasizes the thought Ronggowarsito in Serat Wirid Hidayat Jati and Serat Pamoring Kawula Gusti. Broadly speaking, the spiritual education in both of these fibers include six piwulang namely: the spiritual education based saliimul 'aqidah, spiritual education based on the power of a single, spiritual education based quwwatul faith, spiritual education based pensaksian, spiritual education based on science kasampurnaan and spiritual education based tazkiyatun nafs. The purpose of spiritual education of Java-Islam is substantively strengthen the quality of human spirituality by recognizing the oneness, the glory, the power of God through the efforts to cleanse our hearts and fill them with the nature of merit by doing tapaning bodies, tapaning minds, tapaning hawa lust, asceticism, tapaning suksma, tapaning cahya umancur, tapaning urip. These efforts will not succeed without their spiritual teacher instructions. A teacher in the teaching of spiritual education plays a very vital namely educating the human heart to abide by and adhere to the rules of Allah. For that teachers should have a spirit of compassion, patient, selfless, sensitive, and not arrogant, fine words, polite behavior, steadfast stance, noble sacrifices, sharp thinking, as well as a good sense of devotion.